CHINA'S 'POLITICAL RE-EDUCATION' CAMPS OF XINJIANG'S UYGHUR MUSLIMS. Issue 4 (8th August 2019) - Raza, Zainab
Abstract : Recently, reports have emerged that China operates "political re-education" camps of Uyghur Muslims in Xinjiang. China justified them as a sort of vocational training program to assist Uyghurs in participating in the Chinese economy. In actuality, they are brutal incarceration camps; these forms of 'education' can qualify as torture that perhaps 1.5 million adults have been subjected to, and have led to detaining children of people incarcerated in state-run boarding schools. It is necessary to interrogate the underlying factors that have enabled the Chinese government to open and operate these camps under the guise of education. This paper first examines the impact of the current geopolitical interests of China's Belt & Road Initiative and the historical backgrounds of Xinjiang and the Re-Education through Labour program. It then explains the methods of 'education' taking place within the camps and interrogates China's justifications for building them. This education issue is more about inhibiting Uyghur power than China's claim that the camps are meant to empower Uyghurs to participate in the Chinese labour force.